Pengembangan Aspek Landasan Terhadap Perancangan Kurikulum di Sekolah Dasar - Cappa, Erwin; Hamzah, Rahma Ashari; Intan, Intan (P3M POLITEKNIK NEGERI AMBON, 2024)
This article discusses the development of a foundation for curriculum design in primary schools. A foundation must support the development of the curriculum in order for it to work in accordance with its stated objectives. Guidelines for curriculum design should be included in the curriculum content. The curriculum is a tool for work that is prepared so that the plan can be followed effectively. The research methodology used in this article is the desk research method, which involves collecting information from various online sources, including books and journals. In other words, the desk research method requires a literature review of data sources in the form of books and journals. The purpose of this article is to provide readers with a better understanding of the fundamentals involved in curriculum design. The data collection strategy or data analysis technique uses a qualitative approach, specifically a literature analysis of data from books and journals found on the internet. The results of this study found that there are 4 foundations of curriculum design including, (1) the philosophical foundation, which is used in the creation of the curriculum both as an actual implementation in schools and as a written program, (2) the psychological foundation, to modify teaching to suit the needs of students, starting with the content that needs to be taught and how to teach it, (3) the sociological foundation, which must be adapted to the environment of the community where education is held, including the facilities and infrastructure available, affecting and supporting the implementation of education, (4) the foundation of science and technology, the curriculum must consider industry needs, lifestyles, labor needs and demands, and individual needs in line with advances in science and technology in order to keep pace with these developments. This research will also show how the above foundations can play an important role in curriculum design. Keywords: foundation, design, curriculum